Microhardness evaluation of enamel adjacent to an improved GIC sealant after different enamel pre-treatment procedures - (:unkn) unknown (ARIESDUE SRL, 2014)
Aim This in vitro study was carried out to evaluate the microhardness of enamel adjacent to a glass ionomer cement (GIC) with high fluoride content used as a sealant (Fuji Triage, GC Corp., Japan) after laser, bur or air abrasion treatment procedures. Materials and methods Study design: 200 freshly extracted non-carious human molars were divided into 10 experimental groups according to the enamel pretreatment method: A air abrasion (Mach 4.1 Kreativ Inc., USA); AP, Air abrasion + conditioning with 20% polyacrylic acid (GC cavity conditioner); L, Er, Cr:YSGG laser application (Waterlase, Biolase Technology, Inc., San Clemente, USA); LP, Er, Cr: YSGG laser application and fissure conditioning; B, ameloplasty carried out with a diamond bur especially designed for preparing fissures (Komet #8833); BP, ameloplasty + fissure conditioning; P, application of 20% polyacrylic acid and all fissures sealed with GIC; C, no fissure treatment, the material was applied directly to the fissures (control); R, application of 37% orthophosphoric acid and fissures sealed with a resin-based sealant (Fissurit; Voco, Germany) (control); N, no treatment (control). Half of each group of teeth were left in artificial saliva for one month and the rest for three months. The teeth were then sectioned and microhardness was measured using a Vickers test apparatus. Kruskal-Wallis, Mann-Whitney U and Dunn's multiple comparison tests were carried out (5% significance). Results After one month results regarding hardness at the base and lateral walls of fissures were significantly higher in groups A, AP, L, LP, B, BP, P and C than in groups R and N (p<0.01), but no difference was seen between the treatment procedures. The results after three months produced similar findings with evenly increased values for all groups. Conclusion The results of this study showed that the tested GIC with a higher fluoride content seemed to improve the enamel hardness of the fissure enamel and could be regarded as an alternative material in cases where resin sealant applications are questionable.
Keywords: Air abrasion; Fissure sealant; Glass ionomer cement (GIC); Laser; Microhardness; FISSURE SEALANTS; GLASS-IONOMER; IN-VITRO; MICROLEAKAGE; CARIES; PIT; INHIBITION; PREVENTION; SEM